Globalisation and Education Reforms Creating Effective Learning Environments - Zajda, Joseph; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book analyses discourses of effective learning environments globally. It focuses on the student$1 (Bs cultural identity and academic achievement, the significance of cultural and social capital to student$1 (Bs academic achievement, motivational strategies enhancing engagement and performance, effective teaching strategies, and quality in education for all. The book discusses and evaluates the shifts in methodological approaches to effective learning environments and globalisation. It analyses such topics as the students$1 (Bcultural identity and achievement, motivational strategies for creating effective learning environment, constructivist pedagogy for critical thinking, dimensions of discrimination in schools globally, intelligence testing and the effects on academic achievement, and values education in the classroom. The book evaluates the shifts in methodological approaches to globalisation and effective learning environments globally, and their impact on education policy and pedagogy. It contributes in a very scholarly way, to a more holistic understanding of the nexus between globalisation, comparative education research and effective learning environments education reforms.s
1 Creating Effective Learning Environments in Schools Globally -- 2 Motivation in the Classroom: Creating Effective Learning Environments in Schools -- 3 Constructivist Learning Theory and Creating Effective Learning Environments -- 4 Discrimination and Self-fulfilling Prophecy in Schools Globally -- 5 Current research of theories and models of intelligence globally -- 6 Values Education and Creating Effective Learning Environments: A Global Perspective -- 7 Education quality in schools: Researching dominant paradigms.
Keywords: Education$1 (BCurricula.s; 9; Comparative education; Education and state; Teaching; Educational sociology; Curriculum Studies; International and Comparative Education; Educational Policy and Politics; Pedagogy; Sociology of Education